The Reality of Physical Education Activities in Middle of West Bank Schools from the Point of View of School Principals and Physical Education Teachers - Hamarsheh, Abdelsalam Mohammad; Rabee, Izzaldeen Fawaz (Journal of Educational and Psychological Sciences, 2022)
The present study aims at investigating the reality of physical education activities in Middle of West Bank schools from school principals and physical education teachers point of views. To achieve this goal, the researchers applied the descriptive analytical method as it suits the nature study.The study was carried out during the academic year )2015-2016). The study covered the public, private and UNRWA schools in the education districts of Jerusalem, Jerusalem suburbs, Ramallah and Al-Bireh, Jericho and Jordan Valley schools. The population of the study included )538) male and female principals, as well as )310) male and female physical education teachers. The researcher applied the random stratified sample in selecting )144) principals and )84) teachers who participated in the study.To achieve the aims of the study, the researchers developed a questionnaire to investigate the reality of the activities performed at the schools in Middle of West Bank. The questionnaire included )5) domains with )40) items, whose validity and reliability was tested through applying the appropriate statistical procedures.The study results have shown that the mean is )4.14) which is an indicator of a high level of physical education activities. The domain of planning achieved the highest mean and )4.28) successively, followed by the domains of abilities, implication, evaluation and lastly the domain of incentives. The study results also have shown that there are no statistically significant differences at (α≥0.05 (concerning the reality of physical education activities pertaining to the variables of sex, specialization. Meanwhile, the results of study have shown that there are statistically significant differences at (α≥0.05) pertaining to physical education activities according to the variable of the directorate, and the differences were in favor of the directorate of Jericho and the Jordan Valley.In view of these results, the researchers recommend: That the physical education teachers should reinforce communication skills amongst schools administrations and the parents to enable students to participate in the physical education activities to avoid weak school achievement, and to bridge the gap between teachers and students so as to reinforce partnership and familiarity between them.
Keywords: Physical Education Activities; Mid West Bankn Districts; Principals; Physical Education Teachers